(untitled) (International relations and international law Journal, 2016)
Article is devoted to the contemporary issues of health security. The article says about changing approaches to security studies, reveal the main provisions of the concept of human security as one of the forms of modern security and expanded the concept of «health security» in the ﬁ eld of health.